Pengaruh Citra Merek Terhadap Keputusan Pembelian Konsumen Cemilan Takoyaki Janda Cabang Raun-Raun Food Park Pekanbaru - Maswir, Mulyadi (Eko dan Bisnis: Riau Economic and Business Review, 2024)
The aim of the research is to determine the influence of brand image on consumer purchasing decisions for Takoyaki Janda snacks, Raun-Raun Food Park Pekanbaru branch. The population in this study was 99 people and the research sample was 99 people. The research method used is a descriptive method with a quantitative approach. The average score for the overall statement about Brand Image is 3.48, meaning that the respondent's answer to the statement about the brand image of Janda Takoyaki Snacks, Raun-Raun Food Psark Pekanbaru Branch is in agreement. Meanwhile, respondents' answers to the Purchase Decision statement indicator averaged 3.13, which means quite agree. The data analysis used is simple linear regression with the regression results obtained, namely, Y= 8,645 + 0.614 Based on the results of the t test, it was found that the t value was 4,035 > 1.985 with a significance level of 0.000< 0.05. This means that brand image has a significant influence on buyers' decisions about Janda Takoyaki Snacks, Raun-Raun Food Park Pekanbaru Branch. The R square value is 0.667 or 66.7%. This means that the influence of Brand Image on Purchasing Decisions is 66.7%. Meanwhile, the remaining 33.3% was influenced by other variables outside this research